Parametric study and preliminary transposition of the modal and structural responses of the Tr-FRANCIS turbine at speed-no-load operating condition. (October 2021) - Châteauvert, Thomas; Tessier, Alexandre; St-Amant, Yves; Nicolle, Jonathan; Houde, Sébastien
Abstract: This paper presents results of a fluid–structure analysis of a medium head Francis turbine in speed-no-load regime within the scope of the Tr-FRANCIS project. Tr-FRANCIS aims at identifying and parametrizing damaging fluid–structure interactions in start-up and no-load operation of hydraulic Francis turbines used for power generation. Experimental modal measurements in air first validate part of the numerical methodology used for the simulations. Structural simulations study the impact of flow wall shear stresses on the runner. Results show that shear and pressure loads must be considered to obtain good stress predictions in no-load conditions. Acoustic modal simulations are also performed to evaluate the influence of speed of sound on the modal response. Finally, numerical results are used to study the transposition of the structural and modal responses of a scaled-down runner to production unit. The scaling of the mechanical behavior and modal response indicates a good agreement for the prediction of the static stresses, the frequency content of the dynamic stresses and the natural frequencies in void and in water. Highlights: Wall shear benefits stress prediction of Francis turbines in SNL condition. Speed of sound variations impact the natural frequencies. Transposition of the mechanical behavior succeeds in SNL condition.